Study about Job Satisfaction with Perceived Organizational Support and Quality of Care among Saudi Nurses - Assiri , Salha M.; Shehata, Shehata F.; Assiri, Maha M. (Emerging Trends in Disease and Health Research Vol. 8, 2022)
The current study aimed to assess nurses’ job satisfaction and per- ceived organizational support with their effect on quality of provided health care in Saudi Arabia through assessing direct and indirect relations. Job satisfaction with the quality of given health care is seen as the most important factor that has a direct impact on the health-care industry, since if nurses do not provide excellent treatment to their patients, patient discontent rises. Job satisfaction is described as the degree to which employees are satisfied with their jobs, whether they like the job or specific components of it, such as the sort of work or regulations. A correlational cross-sectional approach was applied to target all accessible nurses who work at the main governmental hospitals in Saudi Arabia during the period from 1st March to 30th April 2020. Data were collected using online questionnaire. Although there was a direct favourable effect of organisational support on the quality of treatment, it was small. Improving the working environment at hospitals and other health-care facilities will result in more loyalty and a sense of security among employees. The primary factors that lead to great job satisfaction with good health care are safety perception and loyalty. Both financial and psychological rewards should be included in organisational assistance.There was a significant relation between organizational support and job satisfaction with their effect on quality of care. Nonsatisfaction was favourably influenced by organisational support, which in turn influenced the quality of treatment provided.